The Prothrombotic Phenotype of Thirdhand Electronic Cigarette Exposure is Sex Independent and Involves Systemic Mediated Effects on Platelet Function: Evidence from a Mouse Model - Shelby S. Umphres; Ahmed B. Alarabi; Hamdy E. A. Ali; Shahnaz Qadri; Fadi T. Khasawneh; Fatima Z. Alshbool (Cardiovascular Toxicology, 2026)
Electronic cigarettes (e-cigs) are major contributors to inflammatory-mediated responses, which are implicated in a vast array of pathophysiological conditions, including cardiovascular disease (CVD). More recently e-cigs have been recognized as a source of thirdhand exposure (THEC); the process by which expelled toxins settle on materials (i.e., carpets, curtains, clothes etc.) and undergo chemical reactions, rendering them more harmful overtime. Herein, mice were exposed to THEC for four months, and platelet reactivity, systemic mediated effects on platelet function, and cytokine expression profiles were analyzed in both sexes. Our data revealed a hyperactive platelet phenotype as determined by shortened bleeding and occlusion times, enhanced platelet aggregation, and dense granule secretion with no significant difference between males and females. Cytokines, amongst other inflammatory molecules, are well documented mediators by which platelet function is modulated and they also enhance susceptibility to CVD. To this end, and to elucidate the mechanism by which platelet reactivity was augmented, washed platelets that were exposed only to clean air (CA) and resuspended in THEC exposed plasma, displayed significantly increased platelet aggregation, dense granule secretion, and p-selectin expression. Indeed, this data suggests that THEC exposure elicits a systemic effect, enhancing platelet response, and was further validated by a dysregulated cytokine profile using plasma, free of platelets, in a sex-dependent manner. Collectively and for the first time, we highlight that both males and females are at similar risk of THEC-mediated prothrombotic phenotype, which is underlined-at least in part- by an indirect systemic effect of exposure on platelet reactivity that involves changes in the cytokine profile. These findings underscore this form of exposure as a threat to cardiovascular health.